Nicolae High - Jenkins, Jerry B.; LaHaye, Tim F. (Wheaton, Ill. : Tyndale House, 1999)
Judd, Vicki, Lionel, and Ryan are back in school, but they are forbidden to talk about the real reason for the disappearance of millions of people.
7.0
5-8
Keywords: Christian life -- Fiction; Eschatology -- Fiction; Fantasy; Schools -- Fiction; Christian life. -- Fiction; Eschatology -- Fiction; School stories; Fantastic fiction